PERAN MODAL SOSIAL PEDAGANG IKAN DI PASAR BERSEHATI MANADO - Duwila, M. Kamel; Kandowangko, Nicolas; Purwanto, Antonius (Universitas Sam Ratulangi, 2020)
Fish in North Sulawesi is the catch of small fishermen and fishing companies, fish caught by large vessels owned by fishing companies are often sold to fish processing plants to be processed and exported abroad as well as those to fishing ports to be sold to suppliers and small traders such as in the Jati fish auction Tuminting District, Fish caught by fishermen with small boats are usually traded in traditional markets. For Manado City, there are several traditional markets and supermarkets that sell fish to consumers directly, one of which is Bersehati Market.The power of social networks facilitates the mobility of trade, where the efforts they are diligent in moving economic resources are needed as well as communication and information for fellow traders. So social relations or networks in the world of trade is very important to be able to meet market demand for traders, especially in the Area of Bersehati Market.Social capital is well maintained especially those who work on average are experienced then the supporting element is also trust. Given that not all the ingredients imported from the fishing were immediately paid but there was an agreement between their fellow suppliers and the fishermen on board, that for the payment of the fish will be repaid when the proceeds of the sale are completed.Â Keywords: market, relationships, social capital